Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires